Getting along how to work with anyone (even difficult people) - Gallo, Amy (Ascent Audio, 2022)
Work relationships can be hard. The stress of dealing with difficult people dampens our creativity and productivity, degrades our ability to think clearly and make sound decisions, and causes us to disengage. In Getting Along, workplace expert and Harvard Business Review podcast host Amy Gallo identifies eight familiar types of difficult coworkers-the insecure boss, the passive-aggressive peer, the know-it-all, the biased coworker, and others-and provides strategies tailored to dealing constructively with each one. She also shares principles that will help you turn things around, no matter who you're at odds with. Taking the high road isn't easy, but Gallo offers a crucial perspective on how work relationships really matter, as well as the compassion, encouragement, and tools you need to prevail-on your terms. She answers questions such as: Why can't I stop thinking about that nasty email?! What's behind my problem colleague's behavior? How can I fix things if they won't cooperate? I've tried everything-what now? Full of relatable, sometimes cringe-worthy examples, the latest behavioral science research, and practical advice you can use right now, Getting Along is an indispensable guide to navigating your toughest relationships at work-and building interpersonal resilience in the process.
Online resource; title from title details screen (O'Reilly, viewed September 20, 2022)
Keywords: Conflict management; Interpersonal conflict; Problem employees -- Psychology; Psychology, Industrial; Gestion des conflits; Conflit interpersonnel; Employés à problèmes; Psychologie; Psychologie du travail; Downloadable audio books; Audiobooks; Livres audio